2007
DOI: 10.1002/dvdy.21103
|View full text |Cite
|
Sign up to set email alerts
|

MyoD and Myogenin expression during myogenic phases in brown trout: A precocious onset of mosaic hyperplasia is a prerequisite for fast somatic growth

Abstract: Muscle cell recruitment (hyperplasia) during myogenesis in the vertebrate embryo is known to occur in three consecutive phases. In teleost fish (including zebrafish), however, information on myogenic precursor cell activation is largely fragmentary, and comprehensive characterization of the myogenic phases has only been fully undertaken in a single slow-growing cyprinid species by examination of MEF2D expression. Here, we use molecular techniques to provide a comprehensive characterization of MyoD and Myogenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 72 publications
3
67
1
1
Order By: Relevance
“…With this study we do not know if mosaic hyperplasia started after the previous phase had ceased or overlapped with stratified growth. The examination of the MyoD and Myogenin (members of the myogenic regulatory family) expression in Salmo trutta lacustris (Linnaeus) showed that the stratified hyperplasia and mosaic hyperplasia began simultaneously and progressed vigorously (Steinbacher et al, 2007). A similar approach can be used in future in Pagellus bogaraveo to clarify this issue.…”
Section: Fry Aged 70-100 Daysmentioning
confidence: 99%
“…With this study we do not know if mosaic hyperplasia started after the previous phase had ceased or overlapped with stratified growth. The examination of the MyoD and Myogenin (members of the myogenic regulatory family) expression in Salmo trutta lacustris (Linnaeus) showed that the stratified hyperplasia and mosaic hyperplasia began simultaneously and progressed vigorously (Steinbacher et al, 2007). A similar approach can be used in future in Pagellus bogaraveo to clarify this issue.…”
Section: Fry Aged 70-100 Daysmentioning
confidence: 99%
“…Hyperplasia was evident within the first week of the experiment by the observation of several small fibers with central nuclei. This morphological feature characterizes skeletal muscle development in mosaic hyperplasia, with small fibers containing central nuclei surrounding big fibers throughout the myotome (Johnston et al 2003;Johnston and Hall 2004;Johnston et al 2008;Steinbacher et al 2007;Valente et al 2013). However, after 10 weeks of refeeding the growth pattern changed, with increasing the frequencies of muscle fibers in the [ 50 lm diameter classes and decreasing the frequencies in the 10 and 30 diameter classes.…”
Section: Discussionmentioning
confidence: 99%
“…Each gene has evolved to regulate a specific area of myogenesis. For instance, MyoD and myf5 are essential regulators of muscle cell proliferation determination, whereas myogenin and myf4 act as regulators of muscle cell differentiation (Rudnicki et al 1993;Steinbacher et al 2007;Johnston et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…By combining nuclear Pax7 expression with ultrastructural analysis of satellite cells, we concluded that Pax7 is a reliable satellite cell marker for S. macrurus. By virtue of their nuclear Pax7 expression, morphology and location, these cells associated with muscle fibers and electrocytes were considered to be homologs of satellite cells observed in mammals (Schultz et al, 2006;Ishido et al, 2009), salamanders (Morrison et al, 2006), frogs (Chen et al, 2006) and other teleosts (Steinbacher et al, 2007). Moreover, these data provided the first example of Pax7-positive muscle progenitor cells localized within a non-contractile electrogenic tissue, representing an exception to the tissue specificity of these myogenic stem cells to striated muscle fibers in vertebrates.…”
Section: Activation Of Myogenic Stem Cells In Response To Tail Amputamentioning
confidence: 91%